1989
DOI: 10.1152/ajpregu.1989.256.3.r612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fasting on glucose turnover in a carnivorous fish (Hoplias sp)

Abstract: Intravenous glucose tolerance tests and measurements with [6-3H]glucose of rate of glucose replacement, transit time, and body glucose mass were performed in fed and fasted Hoplias malabaricus. Both glycemia levels and the rate of decline of blood glucose following intravenous administration of 500 mg/kg glucose were significantly lower in 60-day-fasted than in fed fish. Changes in plasma free fatty acids were opposite to those in blood glucose. The rate of glucose replacement, calculated graphically from mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Several studies have demonstrated that plasma free FA levels increase in fish subjected to fasting regimens (Lewis and Epple, 1984;Machado et al, 1988Machado et al, , 1989Shimeno et al, 1990;Sheridan and Mommsen, 1991;Souza et al, 2000;Figueiredo-Garutti et al, 2002). The elevation in plasma glycerol levels observed in the present study suggest that R. quelen mobilized glycerol from lipid stores (mesenteric, muscle, belly flap, and liver), as has been observed in other fish species (Albalat et al, 2006;Farbridge et al, 1992;Navarro et al, 1992).…”
Section: Experimental Groups I (Control)supporting
confidence: 80%
“…Several studies have demonstrated that plasma free FA levels increase in fish subjected to fasting regimens (Lewis and Epple, 1984;Machado et al, 1988Machado et al, , 1989Shimeno et al, 1990;Sheridan and Mommsen, 1991;Souza et al, 2000;Figueiredo-Garutti et al, 2002). The elevation in plasma glycerol levels observed in the present study suggest that R. quelen mobilized glycerol from lipid stores (mesenteric, muscle, belly flap, and liver), as has been observed in other fish species (Albalat et al, 2006;Farbridge et al, 1992;Navarro et al, 1992).…”
Section: Experimental Groups I (Control)supporting
confidence: 80%
“…The true capacity of fish for glucoregulation could be better assessed by quantifying the plasticity of glucose kinetics rather than by relying on concentration changes during glucose tolerance tests. The first glucose fluxes reported for fish were measured by bolus injection of tracer in kelp bass (Paralabrax clathratus) (Bever et al, 1977(Bever et al, , 1981, skipjack tuna (Katsuwonus pelamis) (Weber et al, 1986), seabass (Dicentrarchus labrax) (Garin et al, 1987), wolf fish (Hoplias malabaricus) (Machado et al, 1989) and brown trout (Salmo trutta) (Blasco et al, 1996). These early studies showed that glucose turnover rate can be strongly reduced by prolonged fasting and that resting glucose fluxes vary with the basal metabolic rate of individual species.…”
Section: Glucose Kinetics and Glucoregulationmentioning
confidence: 99%
“…These observations are based on measurements of blood glucose concentrations that depend on changing rates of appearance in and disappearance from the circulation (R a and R d glucose). Earlier kinetics studies have reported baseline glucose fluxes in kelp bass, sea bass and tuna (Bever et al, 1977;Garin et al, 1987;Weber et al, 1986), as well as changes in flux during glucose tolerance tests in wolf fish and brown trout (Blasco et al, 1996;Machado et al, 1989). However, all these studies have relied on the bolus injection technique, which cannot quantify R a and R d separately.…”
Section: Introductionmentioning
confidence: 99%